MEDIASI SEBAGAI UPAYA PENYELESAIAN PERKARA YANG BERSIFAT KOOPERATIF - SUWANDA, I WAYAN (GANEC SWARA, 2021)
It is estimated that the judicial system will not be able to meet the increasingly complex needs of society. This estimate is based on facts in the field. Dispute resolution through courts is considered too convoluted, takes a long time, and is inefficient for businesses that emphasize efficiency and effectiveness. Besides, the court's decision does not satisfy the parties. The principle of simple, fast, low-cost justice is still only a slogan.      Answering this problem, a study is conducted using the empirical normative legal research method with a study approach based on statutory regulations, conceptual approaches, and case approaches. Types and sources of data used in this study are primary data and secondary data with data collection techniques through document study and interviews, where the data obtained will be analyzed qualitatively deductively. Based on the results of research and discussion, it was found that mediation as a solution to the settlement of cases, both in court and outside the court, is cooperative